Optimizing Yield Components of Canavalia ensiformis through Integrated Pruning and Mycorrhizal Management under Rainfed Conditions - Nurfiyanti; Putra, Riand Adhi (Integrated and Sustainable Agriculture, 2025)
Integrated and sustainable agricultural systems require management strategies that simultaneously optimize crop productivity and biological soil functions, particularly in rainfed and low-input environments. However, empirical evidence linking canopy management and soil biological inputs within a unified system framework remains limited. This study evaluated the integrated effects of pruning management and arbuscular mycorrhizal fungi (AMF) inoculation on the growth, yield components, and root biological responses of Canavalia ensiformis using a factorial randomized complete block design under rainfed conditions. The combined application of leaf pruning and AMF inoculation consistently enhanced yield components, including pod number, pod weight, seed formation, and seed weight, compared with single-factor or control treatments. Integrated management also improved vegetative architecture and significantly increased root nodule formation, indicating strengthened belowground biological processes. The results demonstrate that yield improvement is driven by synergistic interactions between aboveground canopy regulation and belowground symbiotic functions, highlighting the role of biological efficiency in integrated agricultural systems. This study provides novel system-level evidence that integrating pruning and AMF inoculation represents a viable, low-input strategy to enhance productivity and sustainability in rainfed legume-based farming systems.